Low residue or normal diet in Crohn's disease: a prospective controlled study in Italian patients. Issue 10 (October 1985) - Levenstein, S; Prantera, C; Luzi, C; D'Ubaldi, A
Abstract : Seventy patients with non-stenosing Crohn's disease were randomly assigned to follow a low residue diet or a normal Italian diet for a mean of 29 months. The two groups were comparable at the onset in various measures of disease severity and diet. Patients complied well with the diet prescriptions, the low residue group eating a mean of 8.1 portions a week of fibre containing foods and the liberalized group a mean of 26.6 portions (p less than 0.005). There was no difference in outcome between the two groups, including symptoms, need for hospitalisation, need for surgery, new complications, nutritional status, or postoperative recurrence. Eighty six per cent of patients eating ad libitum and 65% of patients who avoided roughage eliminated one or more permitted foods because of subjective intolerance. Lifting of dietary restrictions, which results in a more appetizing and nutritious diet, does not cause symptomatic deterioration or precipitate intestinal obstruction in Crohn's disease.